Scientists, plants and politics: A history of the plant genetic resources movement - Pistorius, R. (1997)
This book is the result the first Vavilov-Frankel fellowship that was awarded in 1993. The Vavilov-Frankel Fellowships programme was established by the Bioversity Board of Trustees in 1989 to commemorate the unique contributions to plant science by academician Nikolai Ivanovich Vavilov of Russia and Sir Otto Frankel of Australia. The first two fellowships examined the historical background of the plant genetic resources movement and produced two books: the present one and the one by Igor Loskutov, Vavilov and his institute: a history of the world collection of plant genetic resources in Russia.